SISTEM MONITORING PADA TRANSFORMATOR ISOLASI - Dwi Nugroho, Bimo; Nursabila, Dhava; Ocsirendi; Saputra, Zanu (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2024)
This research discusses the monitoring system on isolation transformers that play an important role in the electric power system, especially in maintaining operational performance and safety. Isolation transformers are used to separate two parts that are under voltage and protect equipment from electrical interference. The designed monitoring system aims to monitor critical parameters such as voltage, current, and temperature of the transformer in real-time using a TCP/IP-based control module connected to a PC. The methods used include temperature monitoring through sensors that control cooling fans to prevent overheating, as well as monitoring the trip status of electrical loads to detect and prevent electrical faults. The data obtained is displayed through the Node-RED application to facilitate performance analysis. The results show that this system is effective in improving the reliability and safety of transformers with preventive measures against potential damage. The use of modern technology and the integration of an automatic monitoring system not only improves efficiency but also provides a preventive solution to maintain the operational stability of isolation transformers.